Efek Interaksi Kepemimpinan Otentik ─ Kepercayaan Pada Pimpinan Organisasi Terhadap Kepuasan Kerja Tenaga Pendidikan Dan Kependidikan STAI At-Tahdzib Jombang - Ali Audah; Moh. Ulumuddin (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
This study examines employee job satisfaction through authentic leadership practices, organizational-trust in leader and interaction between the two. The study was conducted at the STAI At-Tahdzib Jombang and took 23 educator and adminsitration staff randomly as sample of the study. The data were analyzed by simple regression analysis, multiple regression analysis and moderate regression analysis. The analysis shows authentic leadership has a positive effect on job satisfaction. The positive influence of authentic leadership on job satisfaction is lost when multiple and interacts with organizational-trust in leader. Organizational-trust in leader has a positive effect on job satisfaction. The positive effect of organizational-trust in leader on job satisfaction does not disappear when multiple and interacts with authentic leadership. Organizational-trust in leader has no effect of strengthening or weakening the influence of authentic leadership on job satisfaction. The interaction between authentic leadership and trust in organizational leadership has no effect on job satisfaction.